The Effect of Audiovisual Health-Based Education on Medication compliance among Tuberculosis Patients - Ika Endah Kurniasih; Soedarsono Soedarsono; Laily Hidayati; Maulana Arif Murtadho (International Journal of Nursing and Health Services (IJNHS), 2020)
Tuberculosis (TB) has been around for thousands of years and remains a major global health problem. One of the factors that influence non-compliance in TB treatment is a lack of knowledge about TB and treatment. The study aimed at examining the effect of audiovisual health education on the compliance behavior of tuberculosis patients in taking medication. Methods: This study used a quasi-experimental, pre and post with a control group that was applied in this study. Seventy samples were recruited using nonprobability sampling by means of purposive sampling and divided into two groups (interventions and control groups). Data analysis was performed and presented in descriptive statistics, and significant findings were computed using the paired t-test. Results: The results showed that the mean increase in the medication compliance intervention group from 6,89+ 1,105 to 7,46+0,701 after the intervention. Meanwhile, in the control group, the mean medication compliance level slightly downhill from 6,89+ 1,105 to 7,23+1,060. The paired t-test obtained a p-value of 0.000, indicating that there were significant differences in the enhancement in medication compliance between the intervention and the control group. Conclusion: based audiovisual health education interventions based on the Health Belief Model can improve the compliance behavior of TB patients in taking medication. The nurse profession is expected to be able to use preoperative based audiovisual health education interventions based on the Health Belief Model to become one of the independent nursing interventions.